The Analysis of The Impact of Financial Factors on The Performance of Sharia Stocks - Mahesa Syahrial, sultan; Noor, Sufiana; Andriyanto, Irsad (Faculty of Islamic Economics and Business, State Islamic University of Kiai Haji Achmad Siddiq Jember, Indonesia, 2023)
This research examined the effect of liquidity, solvency, and firm size on profitability in the Food and Beverage sector, listed on the Indonesia Sharia Stock Index (ISSI) for 2017-2021. The research sample was selected using the purposive sampling method. Using E-views 10 software as a test tool, multiple linear regression analyses analyze the relationship between independent and dependent variables. The results showed that liquidity does not affect profitability, solvency affects profitability, and firm size does not. The limitations of this study include the limited number and years of research data using only the Food and Beverage sector. This study reflects investors and management in making financial decisions based on the variables studied.